Hubungan Merokok dan Hipertensi pada Pasien Penyakit Jantung Koroner - Andi Batari Ramadhina; Indah Lestari Daeng Kanang; Theo Deus (Pusat riset dan Inovasi Nasional, 2025)
Coronary Heart Disease (CHD) is the leading cause of death in Indonesia. CHD is a disease caused by blockages in blood vessels (atherosclerosis) that disrupt blood flow to the heart. There are several risk factors for CHD, including smoking and hypertension. The purpose of this study was to determine the relationship between smoking and hypertension in patients with CHD. This research method uses the methodliterature review. Data were obtained from secondary data using documentation techniques. This documentation was done by searching for articles through Google Scholar and Pubmed. The selected articles were in accordance with the research variables and inclusion criteria. The articles were analyzed using the procedurecompare, contrast, criticize, synthesize, dan summarize. From the study, 3 articles were obtained that had data related to smoking and CHD variables (p < 0.05) and 3 articles that had data related to hypertension and CHD variables (p < 0.05). Conclusion: There is a significant relationship between smoking and hypertension in CHD patients.